Tracing nuclear-wave-packet dynamics in singly and doubly charged states of N2 and O2 with XUV pump–XUV probe experiments - Magrakvelidze, Maia; Herrwerth, O.; Jiang, Y. H.; Rudenko, Artem; Kurka, M.; Foucar, L.; Kühnel, K. U.; Kübel, M.; Kling, Nora G.; Schröter, C. D.; Düsterer, S.; Treusch, R.; et al. (My University, 2012)
We traced the femtosecond nuclear-wave-packet dynamics in ionic states of oxygen and nitrogen diatomic molecules employing 38-eV XUV-pump–XUV-probe experiments at the free-electron laser in Hamburg (FLASH). The nuclear dynamics is monitored via the detection of coincident ionic fragments using a reaction microscope and a split-mirror setup to generate the pump and probe pulses. By comparing measured kinetic-energy-release spectra with classical and quantum-mechanical simulations, we identified electronic states of the molecular ions that are populated by ionization of the neutral molecule. For specific fragment charge states, this comparison allows us to assess the relevance of specific dissociation paths.
Keywords: Nuclear-wave-packet dynamics; Molecular ions